MULTIVARIATE ANALYSIS OF PRODUCTION OF PERISHABLE GOODS IN THE STATE OF SÃO PAULO - Putti, F. F.; Macini, N.; Silva, I. P. de F.; Latorre, D. de O.; Silva Junior, J. F. da; Ludwig, R.; Schimitd, A. P. R. A. (Revista Brasileira de Engenharia de Biossistemas, 2014)
Brazil is characterized by great diversity. The fact is not different in the state of São Paulo where several crops are produced in different administrative regions. Current study determines which productions are closer to major consumer centers. A multivariate analysis between production and towns has been applied so that the principal components of this analysis may be assessed. Further, the more perishable products are those which are closer to consuming centers.